Effects of maximum aggregate size on fracture behaviors of self-compacting lightweight concrete. (1st October 2016) - Karamloo, Mohammad; Mazloom, Moosa; Payganeh, Gholamhasan
Highlights: Fracture parameters of SCLC were obtained by SEM. As the maximum aggregate size increased, fracture energy increased. SCLC members must be designed by nonlinear fracture mechanics. Size effect law can predict failure loads of SCLC members with good precision. Brittleness of specimens is affected by w/c ratio and maximum size of aggregate. Abstract: This study considers the influences of maximum aggregate size ( d max ) on fracture parameters and brittleness of self-compacting lightweight concrete. A series of three point bending tests were carried out on 84 notched beams with different sizes. Six compositions with d max = 9.5, 12.5 and 19 mm, and water/cement ratios of 0.35 and 0.4 were considered. In each mix, the parameters were analyzed by size effect method. The results indicated that as d max increased, the fracture toughness and energy increased, which may be explained by changes in fractal dimensions. Moreover, the ductility, measured by means of effective length of fracture process zone, increased.